E-SCM SEBAGAI STRATEGI PENGENDALIAN PERSEDIAAN DI INDUSTRI FURNITURE - Sabilla, Alzena Dona; mahendra, Danang; Azzat, Noor Nailie; Ananta, Yoga Sofian (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
Digitalization and globalization have a big impact on the furniture industry, especially on the MSME scale. A big challenge in managing product inventory efficiently. Mismanagement of product stock can lead to high operational costs and decreased customer satisfaction. This research aims to develop a web-based Electronic Suppy Chain Management (E-SCM) application to improve inventory control in Furniture MSMEs. This application is equipped with main features such as managing products, managing incoming and outgoing stock items, and a dashboard tang displaying stock movements in real time. Case studies were conducted on 10 furniture MSMEs in Jepara, using sales and inventory data for 12 months. Data analysis shows that the application of the E-SCM application increases the accuracy of stock management, reduces the amount of dead stock and accelerates the process of making business decisions. This research is expected to be a reference for E-SCM-based technology development for other MSME sectors.